New ways of polarization control of internal stresses in the optically transparent material parts - Маслов, Володимир Петрович (Eastern-European Journal of Enterprise Technologies, 2013)
The article deals with the problem of the new ways of polarization control of internal stresses in the optically transparent materials details. During the process of growing, the optically transparent materials, such as mono-crystal sapphire ingots, may obtain some defects, e.g. micro-bubbles or the grain boundaries, as well as the mechanical stresses that affect their properties significantly. The aim of this work was to study the new ways to control the polarization of the internal stresses in the optically transparent materials details. In order to implement this task we used a new highly polarized - modulation spectrometry method. This method allows us to measure the local mechanical stresses in the optically transparent materials details with high sensitivity, and the usage of the reflected sunlight enables to control the internal stresses in the sheet glass of a large size. As such, the usage of the LCD as a source of light polarization was introduced for the first time. The point is that the intensity of sunlight depends on the weather conditions, and that factor affects the results of the research.